2015
DOI: 10.1007/s12011-015-0474-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tauroursodeoxycholic Acid and 4-Phenylbutyric Acid on Metabolism of Copper and Zinc in Type 1 Diabetic Mice Model

Abstract: Alternations of copper (Cu) and zinc (Zn) status in diabetes have received a great attention. Tauroursodeoxycholic acid (TUDCA) and 4-phenylbutyric acid (PBA) could alleviate the increased endoplasmic reticulum (ER) stress and prevent insulin resistance. This study aimed to investigate the effect of TUDCA and PBA on metabolism of Cu and Zn in diabetic mice model. Diabetes was induced by streptozotocin in FVB mice treated with and without TUDCA and PBA. Determination of Cu and Zn in tissues and serum by acid di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…Interestingly, the latest studies suggest a novel UPR-independent mechanism of TUDCA beneficial activity in type 1 diabetes, consisting of the regulation of micronutrients metabolism [117,118]. These studies imply an important role of Mg 2+ and Ca 2+ [118], as well as Cu 2+ and Zn 2+ [117] in glycemic control in type 1 diabetic mice models.…”
Section: Tudca In Diabetes and Obesitymentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, the latest studies suggest a novel UPR-independent mechanism of TUDCA beneficial activity in type 1 diabetes, consisting of the regulation of micronutrients metabolism [117,118]. These studies imply an important role of Mg 2+ and Ca 2+ [118], as well as Cu 2+ and Zn 2+ [117] in glycemic control in type 1 diabetic mice models.…”
Section: Tudca In Diabetes and Obesitymentioning
confidence: 97%
“…Interestingly, the latest studies suggest a novel UPR-independent mechanism of TUDCA beneficial activity in type 1 diabetes, consisting of the regulation of micronutrients metabolism [117,118]. These studies imply an important role of Mg 2+ and Ca 2+ [118], as well as Cu 2+ and Zn 2+ [117] in glycemic control in type 1 diabetic mice models. It has been shown that levels of these microelements were altered significantly during the progress of diabetes, and long-term administration of TUDCA restored Mg 2+ , Ca 2+ , Cu 2+ , and Zn 2+ levels to normal values [117,118].…”
Section: Tudca In Diabetes and Obesitymentioning
confidence: 97%
“…For example, through specifically reduction in microglial reactivity, TUDCA can inhibit microglial migration in mice hippocampus [25] and prevent retinal degeneration [26]. TUDCA is also regarded as an inhibitor of ER stress, whose inhibition has been well-documented to mediate the protective effects of TUDCA on diabetes, obesity, and major depression [27][28][29]. Within these contexts, we hypothesize that TUDCA may have antidepressantlike activities, and attenuation of neuroinflammation, oxido-nitrosative stress, or ER stress may be a core mechanism for the antidepressant-like effect of TUDCA.…”
Section: Introductionmentioning
confidence: 99%
“…TUDCA is approved by the U.S. Food and Drug Administration for use in biliary cirrhosis, and it is used effectively for cholestatic liver diseases11. Recent studies have revealed that TUDCA has an ameliorating effect on several diseases, including neurodegenerative diseases, osteoarthritis, vascular diseases, and diabetes12131415. In addition, TUDCA regulates stem cell differentiation into various lineages such as adipogenic and osteogenic lineages1617.…”
mentioning
confidence: 99%